IMPLEMENTASI SISTEM INFORMASI PEMBAYARAN SPP BERBASIS ANDROID DENGAN PAYMENT GATEWAY MIDTRANS - Hariselmi, Hariselmi; Ilmi, Miftahul; Andema, Henky; Habibie, Dedi Rahman (JURSIMA, 2022)
The school is an educational institution that runs with tuition fees used by its students. During the Covid 19 pandemic which limits human mobility, this does not affect the obligation to pay tuition fees by students, in a payment information system that is able to overcome this problem, it is urgently needed. An Android-based Payment Information System with a midtrans payment gateway is the solution to this problem. This information system provides payment applications for education without direct meetings between the parents of students and the school. This application has two levels of users, namely admin user and student user. The admin user has the responsibility to manage the application as a whole, including more new students, more billing for each student, payment reports made by students on the system. Users are given access rights to view billing that must be started, view transactions that have been made and make changes to personal data if an error occurs in data input. This application is expected to be a solution for educational institutions in overcoming problems that are now commonly found and able to open people's minds in the process of digitizing life. Keywords: Information Systems, Midtrans, Payment Gateway